Conserved NPPB+ Border Zone Switches From MEF2- to AP-1–Driven Gene Program. Issue 10 (3rd September 2019) - van Duijvenboden, Karel; de Bakker, Dennis E.M.; Man, Joyce C.K.; Janssen, Rob; Günthel, Marie; Hill, Matthew C.; Hooijkaas, Ingeborg B.; van der Made, Ingeborg; van der Kraak, Petra H.; Vink, Aryan; Creemers, Esther E.; Martin, James F.; et al.
Abstract : Background: Surviving cells in the postinfarction border zone are subjected to intense fluctuations of their microenvironment. Recently, border zone cardiomyocytes have been specifically implicated in cardiac regeneration. Here, we defined their unique transcriptional and regulatory properties, and comprehensively validated new molecular markers, including Nppb, encoding B-type natriuretic peptide, after infarction. Methods: Transgenic reporter mice were used to identify the Nppb -positive border zone after myocardial infarction. Transcriptome analysis of remote, border, and infarct zones and of purified cardiomyocyte nuclei was performed using RNA-sequencing. Top candidate genes displaying border zone spatial specificity were histologically validated in ischemic human hearts. Mice in which Nppb was deleted by genome editing were subjected to myocardial infarction. Chromatin accessibility landscapes of border zone and control cardiomyocyte nuclei were assessed by using assay for transposase-accessible chromatin using sequencing. Results: We identified the border zone as a spatially confined region transcriptionally distinct from the remote myocardium. The transcriptional response of the border zone was much stronger than that of the remote ventricular wall, involving acute downregulation of mitochondrial oxidative phosphorylation, fatty acid metabolism, calcium handling, and sarcomere function, and the activation of a stress-response program. Analysis of infarcted human hearts revealed that the transcriptionally discrete border zone is conserved in humans, and led to the identification of novel conserved border zone markers including NPPB, ANKRD1, DES, UCHL1, JUN, and FOXP1 . Homozygous Nppb mutant mice developed acute and lethal heart failure after myocardial infarction, indicating that B-type natriuretic peptide is required to preserve postinfarct heart function. Assay for transposase-accessible chromatin using sequencing revealed thousands of cardiomyocyte lineage-specific MEF2-occupied regulatory elements that lost accessibility in the border zone. Putative injury-responsive enhancers that gained accessibility were highly associated with AP-1 (activator protein 1) binding sites. Nuclear c-Jun, a component of AP-1, was observed specifically in border zone cardiomyocytes. Conclusions: Cardiomyocytes in a discrete zone bordering the infarct switch from a MEF2-driven homeostatic lineage-specific to an AP-1–driven injury-induced gene expression program. This program is conserved between mouse and human, and includes Nppb expression, which is required to prevent acute heart failure after infarction. Abstract : Supplemental Digital Content is available in the text.